Copyright Limitations within Film Review Content on YouTube Under Law Number 28 of 2014 on Copyright - Atfan, Dzikrina Khusnaliani; Praja, Chrisna Bagus Edhita; Heniyatun, Heniyatun (Borobudur Law and Society Journal, 2025)
The development of technology makes access to information and communication easier. YouTube is a video sharing platform that widely used to share information about the world of entertainment, including films. This research aims to examine the suitability of film review content uploaded on YouTube with the principle of copyright limitations as stipulated in the Copyright Act. This research uses normative juridical method with statutory approach and concept approach. The results show that film review content can meet the principle of copyright limitation on the condition that it does not activate the monetisation feature provided by YouTube. The monetisation feature is a form of commercialisation that violates copyright limitations in accordance with the provisions stipulated in the Copyright Act.